Antitumor Activity of Balanitoside Extracted from Balanites aegyptiaca Fruit - Sheikha M. Al-Ghannam, Hanaa Hamdy Ahmed, Nabila Zein, Faten Zahran (Journal of Applied Pharmaceutical Science, 2013)
The current study aimed at investigating the antitumor efficacy of balanitoside extracted from Balanites aegyptiaca fruit against Ehrlich ascites carcinoma (EAC) bearing Swiss albino mice. The extracted balanitoside was proved by chemical analysis and LD50 of balanitoside was determined. Then, mice were injected intraperitoneally with balanitoside (10mg /kg b.wt) before and after EAC inoculation, to achieve preventive and therapeutic effects daily, for 9 days. The effects of balanitoside on the count of EAC cells and life span prolongation were studied; malondialdehyde (MDA), nitric oxide (NO) levels as well as catalase (CAT) and caspase 3 activities were estimated. Cytological studies on EAC cells and histopathological examination of liver tissue were carried out. Treatment with balanitoside decreased EAC cell count for preventive and therapeutic groups. MDA and NO levels were decreased in liver and serum in preventive and therapeutic groups compared to positive control group. While CAT activity was increased in liver and plasma of preventive and therapeutic groups in comparison with positive control group. Caspase 3 activity in EAC cells, was increased in preventive and therapeutic groups in comparison with positive control group. Survivin expression in liver was decreased in preventive and therapeutic groups in comparison with positive control group. The present work indicates that balanitoside isolated from fruit extract of Balanites aegyptiaca may possess significant antitumor and antioxidant activity in vivo.
Keywords: Balanites aegyptiaca, EAC, Antitu